The Behavioral Relevance of Landmark Texture for Honeybee Homing - Dittmar, Laura; Egelhaaf, Martin; Stürzl, Wolfgang; Boeddeker, Norbert (Frontiers in Behavioral Neuroscience, 2011)
Honeybees visually pinpoint the location of a food source using landmarks. Studies on the role of visual memories have suggested that bees approach the goal by finding a close match between their current view and a memorized view of the goal location. The most relevant landmark features for this matching process seem to be their retinal positions, the size as defined by their edges, and their colour. Recently, we showed that honeybees can use landmarks that are statically camouflaged, suggesting that motion cues are relevant as well. Currently it is unclear how bees weight these different landmark features when accomplishing navigational tasks, and whether this depends on their saliency. Since natural objects are often distinguished by their texture, we investigate the behavioural relevance and the interplay of the spatial configuration and the texture of landmarks. We show that landmark texture is a feature that bees memorise, and being given the opportunity to identify landmarks by their texture improves the bees’ navigational performance. Landmark texture is weighted more strongly than landmark configuration when it provides the bees with positional information and when the texture is salient. In the vicinity of the landmark honeybees changed their flight behaviour according to its texture.